The Representation of the Seven Elements of Culture in the Novel Janji di Tanah Jawa by Agil Sri Rahayu - Ifana Dwi Ratna Suri; Iib Marzuqi; Miftahul Huda (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to describe the representation of seven cultural elements in the novel Janji di Tanah Jawa by Agil Sri Rahayu based on the concept of seven cultural elements according to Koentjaraningrat. The study uses a qualitative approach with a descriptive method in interdisciplinary comparative literary studies. The research data source is the novel Janji di Tanah Jawa by Agil Sri Rahayu, while the research data are in the form of quotations that represent cultural elements. Data collection techniques are carried out through intensive reading activities, recording, classifying, and documenting data, while data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the novel completely represents the seven cultural elements according to Koentjaraningrat, namely (1) language shown through the use of Javanese krama as a marker of politeness and social stratification; (2) a knowledge system depicted through the use of plants as traditional medicine; (3) social organization that shows social stratification, position, and division of roles in society; (4) a system of living equipment and technology reflected in the use of horse-drawn carriages, traditional writing tools, and traditional clothing; (5) a livelihood system realized through plantation activities, trade, and agricultural processing; (6) a religious system that displays a blend of Islamic teachings with beliefs in ancestors, dreams, and the Javanese calendar; and (7) art represented through gamelan as a traditional Javanese musical art. The research findings show that the novel Janji di Tanah Jawa not only functions as a literary work, but also as a medium for representation and preservation of Javanese culture that shows the close relationship between literary works and the socio-cultural realities of society.